ELECTROCARDIOGRAPHY CHANGES IN PATIENTS WITH ACUTE DIPHTHERIC MYOCARDITIS - Shystval, N.F.; Maliy, V.P.; Polykchi, А.К.; Ryspaeva, D.E.; Dmitrenko, V.М. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Electrocardiography changes in dynamics in 146 patients with diphtheritic myocarditis have been studied. The most often pathology was: sinus bradycardia for 48,7 %, sinus tachycardia for 32,3 %, atrial extrasystolia for 23,5 %, ventricular extrasystolia for 38,7 %, atrial Bouveret's disease for 9 %, ventricular Bouveret's disease for 5 %, atrioventricular blockage I degree - for 19 %, II degree - for 8,5 %, III degree - for 5,4 %, blockage of a dextral leg of a ventriculonector - for 13,2 %, left-hand leg - for 22,6 %. The blockage of the left-hand leg of a ventriculonector was accompanied by a cardiomegaly with considerable violations of hemodynamics. Electrocardiography investigation is a quite informative method in diagnostic of complications on the part of a cardiac muscle in patients with diphtheria.